Potential Efficiency of Digital Technology in Teaching and Learning Latin - Stojcevski, Martina; Nikolic, Agneza; Kisicek, Sanja (2024 47th MIPRO ICT and Electronics Convention (MIPRO), 2024)
The paper encapsulates the possibilities and benefits of ICT in Latin language teaching and learning. First, a general overview is given of current knowledge about the benefits of digital technology in education and the existing issues of using ICT in teaching. An emphasis is placed on the research on the use of multimedia and digital technologies in teaching and learning Latin. Furthermore, the relevant research of the use of ICT in Latin teaching is highlighted and research is conducted on the benefits and frequency of using ICT in Latin teaching in secondary schools in Zagreb and the surrounding area. The results show that there is a large population of students who use ICT in teaching and learning Latin. The potential benefits of different media for learning Latin and other subjects in the context of interdisciplinary and holistic approach to learning are discussed. Finally, the conclusion presents the importance of encouraging further experimental research in the field of learning Latin with the help of multimedia. The possibility of developing cross-curricular topics is discussed.